Survey of Physicians Concerning the Use of Chest Radiography in the Diagnosis of Pneumonia in Out-Patients - Thomas J Marrie (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine how physicians use chest radiography in the diagnosis of pneumonia in ambulatory patients.